1982
DOI: 10.1128/aac.22.2.277
|View full text |Cite
|
Sign up to set email alerts
|

Production, purification, and preliminary characterization of a gonococcal growth inhibitor produced by a coagulase-negative staphylococcus isolated from the urogenital flora

Abstract: Coagulase-negative staphylococcus no. 7, isolated from the urogenital flora, was grown on semisolid brain heart infusion medium. Supernatants were obtained by centrifuging frozen and thawed media which had supported the growth of the staphylococci at 37 degrees C. The kinetic of production revealed that the antigonococcal activity was detected at the end of the logarithmic phase of growth and that the maximum activity was obtained after 24 h of incubation. Production of inhibitory activity was detected in cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…3b). The amino acid sequence of this peptide was found to be similar (54 to 76% amino acid identity) to three highly related peptides (63) originally identified in Staphylococcus haemolyticus as a "gonococcal growth inhibitor" (1). Since that time, these peptides have been found in a number of coagulase-negative staphylococci that exhibit a synergistic zone of complete hemolysis with betahemolysin-producing strains on sheep blood, much like the delta-hemolysin of S. aureus (15,16,29).…”
Section: Resultsmentioning
confidence: 99%
“…3b). The amino acid sequence of this peptide was found to be similar (54 to 76% amino acid identity) to three highly related peptides (63) originally identified in Staphylococcus haemolyticus as a "gonococcal growth inhibitor" (1). Since that time, these peptides have been found in a number of coagulase-negative staphylococci that exhibit a synergistic zone of complete hemolysis with betahemolysin-producing strains on sheep blood, much like the delta-hemolysin of S. aureus (15,16,29).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has recently been shown that specific S. epidermidis PSMs, S. epidermidis PSM␦ and ␦-toxin (PSM␥), have antimicrobial activities against Streptococcus pyogenes owing to their capacity to form pores in the bacterial cell membrane (22). Finally, antimicrobial activities have been detected sporadically for other staphylococcal PSM-like peptides (23). Whether S. aureus PSMs are antimicrobial and responsible for antimicrobial activities exhibited by some S. aureus strains is unknown.…”
mentioning
confidence: 99%
“…The production and purification of the gonococcal inhibitor were carried out as previously described (Beaudet et al, 1982 Elution was with an acetonitrile gradient (1 %/min) at 1.5 ml/min from a Synchropak RP-P column equilibrated in 0.05 % trifluoroacetic acid. The letter T denotes trypsin cleavage.…”
Section: Materials and Methods Bacterial Strainsmentioning
confidence: 99%
“…7 was used for the production of the bactericidal inhibitor (Bisaillon et al, 1980;Lafond et al, 1981;Beaudet et al, 1982). The reference target strain was Neisseria gonorrhoeae G-10 and it was cultivated as previously described (Frenette et al, 1984).…”
Section: Materials and Methods Bacterial Strainsmentioning
confidence: 99%
See 1 more Smart Citation